The oncological outcomes of postoperative radiotherapy in patients with stage II and III upper rectal cancer - ALSAN ÇETİN, İLKNUR (My University, 2022)
Objective: We assessed the oncological outcomes of postoperative radiotherapy and chemotherapy in patients with stage II or III upper rectal cancer who had undergone curative surgery. Patients and Methods: We retrospectively investigated 133 patients who underwent primary curative resection of stage II or III upper rectal cancer. The median age was 62 years (range 30–82 years). Among these patients, 48% were stage II and 52% stage III. All received postoperative radiotherapy, and most received adjuvant 5-fluorouracil-based chemotherapy for 6 months after radiotherapy ceased. Survival curves were plotted using the Kaplan–Meier method, and survival was compared using the log-rank test. Results: The median follow-up was 71.4 months. The 5-year local recurrence-free survival, cancer specific survival, and overall survival (OS) rates were 91.6%, 80.6%, and 75.4%, respectively. Nodal stage 2 (p = 0.02, p = 0.05) was a significant predictor of poor local recurrence-free survival and cancer specific survival rates. In the multivariate analysis, older age (p = 0.01) and a higher N stage (p = 0.01) were independent risk factors for poor OS. Conclusion: The nodal state was predictive of all endpoints in patients with upper rectal stage II or III cancer.
Keywords: TIP, GENEL & DAHİLİ; Klinik Tıp; Klinik Tıp (MED); MEDICINE, GENERAL & INTERNAL; CLINICAL MEDICINE; Clinical Medicine (MED); Upper rectal cancer; Postoperative radiotherapy; Outcomes; PREOPERATIVE RADIOTHERAPY; LOCAL RECURRENCE; SURVIVAL; ADENOCARCINOMA; SURGERY; IMPACT; COLON; Upper rectal cancer; Postoperative radiotherapy; Outcomes